Grammatical Gender Patterns in Contemporary Arabic Medical Terminology: A Morphological Analysis of Arabic Newspaper Articles - Aufa Alfian Musthofa; Sandidu Sangidu; Hendrokumoro Hendrokumoro; Alif Cahya Setiyadi (Ijaz Arabi Journal of Arabic Learning, 2026)
The dynamics of the development of medical terminology in Arabic raise grammatical issues related to gender, specifically the distinction between masculine and feminine. The difference between morphological forms and syntactic behaviour leads to variations in gender usage in contemporary Arabic media texts. This trend marks the transformation of the lexical system, necessitating a review of the gender classification framework. Therefore, a systematic morphological and syntactic analysis is needed to explain the consistency and function of grammatical gender in modern scientific terms. This research aims to categorize the types of masculine and feminine gender in medical terms at the morphological and syntactic levels, and to describe the characteristics of gender classification in Arabic, particularly in loanwords, through a corpus-based approach that combines morphological and syntactic analysis within a unified analytical framework. This research employs a qualitative descriptive approach grounded in corpus linguistics. Data were collected from the newspapers An-Nahār and Akhbārul Yaum, then analyzed using the observation method, specifically the free conversation observation technique and the note-taking technique. Data analysis was conducted using the intralingual equivalence method and the distributional method with a top-down technique. The entire process of data collection and analysis is supported by Sketch Engine as a web-based linguistic corpus software, enabling the empirical mapping of gender usage patterns in modern Arabic journalistic discourse. The research findings indicate that morphologically, the types of mudzakkar are haqiqi, majazi, lafdzi, ma’nawi, and dzati, while the types of mu`annats are haqiqi, majazi, lafdzi, ma’nawi, dzati, and sima’i. The classification at the morphological level is influenced by biological sex, the presence of gender markers, gender forms in meaning, and language conventions. Meanwhile, at the syntactic level, the types of mudzakkar and mu`annats are divided into two types, namely ta’wili and hukmi, which are determined by lexical collocation. This research enriches the study of modern Arabic grammar by providing a grounded understanding of noun gender based on corpus data from medical terminology. In addition, the findings of this research can serve as a reference for Arabic language enthusiasts and speakers in consistently and accurately determining the gender of modern terms. This research also has implications for language planning and the compilation of terminology dictionaries based on empirical evidence.